2017
DOI: 10.1007/s11103-017-0658-9
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq analysis provides insight into reprogramming of culm development in Zizania latifolia induced by Ustilago esculenta

Abstract: We report a transcriptome assembly and expression profiles from RNA-Seq data and identify genes responsible for culm gall formation in Zizania latifolia induced by Ustilago esculenta. The smut fungus Ustilago esculenta can induce culm gall in Zizania latifolia, which is used as a vegetable in Asian countries. However, the underlying molecular mechanism of culm gall formation is still unclear. To characterize the processes underlying this host-fungus association, we performed transcriptomic and expression profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 64 publications
3
48
1
Order By: Relevance
“…Many catalytically active DEGs in infected gall were abundantly expressed throughout the formation of gall formation, which may be related to the survival and gall cell proliferation of pathogenic fungi in host tissues [35]. Among 25 DEGs (Table S6) esculenta infection and gall expanse, GO and KEGG enrichment analysis indicated that most DEGs were classified into response to an endophytic fungal infection pathways including plant hormone signal transduction (Ko04075), phenylpropanoid biosynthesis (Ko00940), starch and sucrose metabolism (Ko00500) consistent with the results of Wang [36]. In our study, we paid close attention to the changes in biological processes and found that U. esculenta can cause plants to respond to stimulus (Fig.…”
Section: Z Latifolia Rna-seq Analysis Reveal Degs Induced By U Escusupporting
confidence: 81%
“…Many catalytically active DEGs in infected gall were abundantly expressed throughout the formation of gall formation, which may be related to the survival and gall cell proliferation of pathogenic fungi in host tissues [35]. Among 25 DEGs (Table S6) esculenta infection and gall expanse, GO and KEGG enrichment analysis indicated that most DEGs were classified into response to an endophytic fungal infection pathways including plant hormone signal transduction (Ko04075), phenylpropanoid biosynthesis (Ko00940), starch and sucrose metabolism (Ko00500) consistent with the results of Wang [36]. In our study, we paid close attention to the changes in biological processes and found that U. esculenta can cause plants to respond to stimulus (Fig.…”
Section: Z Latifolia Rna-seq Analysis Reveal Degs Induced By U Escusupporting
confidence: 81%
“…A higher level of cis-zeatin riboside was detected in the Z. latifolia gall compared to the uninfected shoot [ 8 ]. Furthermore, ZlIPT , the most important enzyme to catalyze cytokinins synthesis, was more highly expressed in gall tissue compared to the uninfected shoot [ 31 ]. Collectively, cytokinins may play a key role in Z. latifolia gall formation and the cytokinins produced by Z. latifolia and/or Ustilago esculenta could stimulate cell division and enlargement, facilitating gall formation.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to other endophytic fungi, U. esculenta infection does not cause leaf chlorosis or death [ 14 , 15 , 16 ]. During the period of culm gall formation, U. esculenta secretes plant hormones, such as auxin and cytokinin, to stimulate gall formation [ 20 , 21 ]. Environmental factors such as temperature, sunlight, and fertilizer use affect the swollen culm yield [ 16 , 22 ].…”
Section: Morphological Characteristics Of the Z Latifolmentioning
confidence: 99%